The Impact Of Non-Performing Loans, Credit Interest Rates And Total Public Savings On Commercial Bank Loan Distribution - Kartini, Kartini; Pratiwi, Sulistya Rini; Irna, Rizky Agusriyanti; Rahmawati, Meylin; Nainggolan, Yohanna Thresia (Universitas Negeri Yogyakarta, 2025)
This study aims to analyse the effect of non-performing loans (NPLs), lending rates, and public savings on lending by commercial banks in North Kalimantan Province. The method used is a quantitative approach with secondary data from Bank Indonesia (BI) and the Financial Services Authority (OJK) in the form of monthly data for the period 2017–2022. The analysis was conducted using multiple linear regression with the assistance of Stata software. The results of the study indicate that NPLs do not have a significant effect on credit disbursement, either for working capital loans or investment loans. Credit interest rates do not affect working capital loans, but have a significant effect on investment loans. Meanwhile, public savings have a significant effect on credit disbursement for both types of loans. Simultaneously, all three variables have a significant impact on credit disbursement. These findings indicate that public savings are the primary factor in increasing credit disbursement, while NPLs are not the main obstacle. Additionally, interest rates have a greater impact on investment loans compared to working capital loans. These results can serve as a reference for banks in formulating credit disbursement strategies and for regulators in developing more effective banking policies.